ANALYSIS OF THE ESTABLISHMENT AND FUNDING OF FEDERAL STATE ENTERPRISES OF AIRPORT ACTIVITY IN NORTHERN AND DISTANT REGIONS OF THE RUSSIAN FEDERATION - A. A. Fridlyand; A. P. Chubukov; P. I. Moskalenko (Научный вестник МГТУ ГА)
This article analyses the processes of creation and functioning of Federal enterprises of airport activity, located in regions of the Far North and similar areas.